RECONSTRUCTION OF THE CRIMINAL SANCTION POLICY AND ACTION (DOUBLE TRACK SYSTEM) IN LAW ENFORCEMENT FOR NARCOTIC CRIME PREVENTION REFFERED TO RELIGIOUS JUSTICE - Carto Nuryanto (Jurnal Pembaharuan Hukum, 2018)
Narcotics abuse is a dangerous problem that can impede the progress of the Indonesian nation in implementing development in every sector of life. Where we know that Indonesia in the decade of the '70s had not yet become a lucrative area for drug marketing. At that time, this country is only a transit area for illicit goods to be shipped to Australia or to other Asia Pacific countries. But two decades later, Indonesia has become a lucrative market for the drug dealers. Even touted to be producers of goods that can make sense of hovering it. The problems faced today are related to the drug is that North Sumatra ranked third after Jakarta and East Kalimantan in the rate of drug users. Setting up a rehabilitation center for criminals, especially drug is a solution. They need the healing process of the illicit drug dependence. Jail is not the best solution for this problem, hold but also perform medical therapy before going to work and we call it “double track system”. It's no secret that many drug users in Penitentiary but still drug dependence. This is because they just physically restrained but the disease has not been cured. They need treatment that has not been achieved. It's no secret that many drug users in Penitentiary but still drug dependence. This is because they just physically restrained but the disease has not been cured. They need treatment that has not been achieved. It's no secret that many drug users in Penitentiary but still drug dependence. This is because they just physically restrained but the disease has not been cured. They need treatment that has not been achieved.